The development of the gut microbiome and temperament during infancy and early childhood: A systematic review. Issue 7 (13th July 2022) - Alving‐Jessep, Emma; Botchway, Edith; Wood, Amanda G.; Hilton, Anthony C.; Blissett, Jacqueline M.
Abstract: Temperament in early childhood is a good predictor of later personality, behavior, and risk of psychopathology. Variation in temperament can be explained by environmental and biological factors. One biological mechanism of interest is the gut microbiome (GM), which has been associated with mental and physical health. This review synthesized existing literature evaluating the relationship between GM composition and diversity, and temperament in early life. Web of Science, PsycInfo, PubMed, and Scopus were searched, and data were extracted according to PRISMA guidelines. In total, 1562 studies were identified, of which six remained following application of exclusion/inclusion criteria. The findings suggest that there is an association between higher alpha diversity and temperament: greater Surgency/Extraversion and High‐Intensity Pleasure in males, and lower Effortful Control in females. Unique community structures (beta diversity) were found for Surgency/Extraversion in males and Fear in females. An emerging pattern of positive temperament traits being associated with GM communities biased toward short‐chain fatty acid production from a metabolism based on dietary fiber and complex carbohydrates was observed and is worthy of further investigation. To gain deeper understanding of the relationship, future research should investigate further the functional aspects of the microbiome and the influence of diet.